2021
DOI: 10.1109/lgrs.2020.3003084
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of the Annular Solar Eclipse of 26 December 2019 and Its Impact on Land– Atmosphere Interactions Over an Arid Region

Abstract: The impact of 26 December 2019 annular solar eclipse (ASE) on meteorological conditions over the southeastern Arabian Peninsula is investigated. Observations sourced from the spinning enhanced visible and infrared imager (SEVIRI) and vertical temperature profiles measured by a microwave radiometer were used. The ASE, which began at 03:36:37.9 Universal Time Coordinated (UTC), that is, 31 m 29.9 s after sunrise, left a significant imprint on the land surface temperature (LST). In particular, in some regions, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…Overall, in conclusion, for the first time, our study reported the impact of the solar eclipse on various meteorological parameters and trace gases measurements at a high-altitude background station in Taiwan. The observed changes in the meteorological parameters at LABS during the annular solar eclipse matched well with the previously reported studies (Anderson, 1999;Ratnam et al, 2010;Nelli et al, 2020). However, compared to the ground-based surface stations (i.e., Naja and Lal, 1997;Tzanis et al, 2008;Girach et al, 2012;Jain et al, 2020), a higher time lag was noticed for the maximum drop in the ozone from the full phase of the eclipse.…”
Section: Discussionsupporting
confidence: 90%
“…Overall, in conclusion, for the first time, our study reported the impact of the solar eclipse on various meteorological parameters and trace gases measurements at a high-altitude background station in Taiwan. The observed changes in the meteorological parameters at LABS during the annular solar eclipse matched well with the previously reported studies (Anderson, 1999;Ratnam et al, 2010;Nelli et al, 2020). However, compared to the ground-based surface stations (i.e., Naja and Lal, 1997;Tzanis et al, 2008;Girach et al, 2012;Jain et al, 2020), a higher time lag was noticed for the maximum drop in the ozone from the full phase of the eclipse.…”
Section: Discussionsupporting
confidence: 90%
“…We found that the local weather and geographical conditions of the two eclipse observation sites were different such that it had an impact on the overall air temperature and humidity results. Considering that other authors have published results on atmospheric effects of the recent annular eclipse of 2019 in the Arabian Peninsula but in Abu-Dhabi (United Arab Emirates) and Oman [7] we will try, additionally, to perform a comparison as far as possible with their observations. These twenty-first century solar eclipses cited above are not the first observed scientifically from the Near East or even in the region of the southern Mediterranean basin (northern Africa).…”
Section: Introductionmentioning
confidence: 99%
“…While there was some haze on the horizon, the weather conditions were optimal to see the whole eclipse. For Riyadh, the observations were made at the King Saud University observatory, while the weather parameters measurements were recorded at the King Abdulaziz City for Science and Technology (KACST) campus (24 A description of soil texture and topography of the Arabian Peninsula area where the 26 December 2019 was viewed (Al-Hofuf) is given by Nelli et al (2020a) [7]; their Figure 1 shows that around Four Mountains Camp in the upper side of the eclipse's central line, the soil is made of sandy loam and loamy sand. In the lower or opposite side of this line, the soil is made of sandy clay and clay loam.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations